(untitled) (World Bulletin of Management and Law, 2022)
The scientific article comparatively studies the scientific and theoretical aspects of raising legal awareness and culture in society, the reforms implemented at its modern stage. Also, in recent years, the activities of the internal affairs bodies in the formation of legal education and culture of the population and the tasks for the future have been analyzed in detail.